Kinetic Study of Photocatalytic Degradation of Tolonium Chloride Under High Pressure Irradiation in Aquatic Buffer Systems - M. Montazerozohori; S. Nezami; S. Mojahedi (E-Journal of Chemistry)
Anatase titanium dioxide catalyzed photodegradation of tolonium chloride at various bufferic pH of 2, 7, 9 and 12 in aqueous solution is presented. The effect of some physicochemical parameters such as initial concentration of dye, catalyst amount and reaction time on photocatalytic degradation has been investigated in a photo-reactor cell containing high pressure mercury lamp to obtain the optimum conditions in each bufferic pH at constant temperature. A complete spectrophotometric kinetic study of tolonium chloride under high pressure irradiation at buffer media was performed. The photocatalytic degradation observed rate constants (kobs) were found to be 2.90×10-3, 3.30×10-3, 3.20×10-3 and 5.20×10-3 min-1 for buffer pH of 2-12 respectively. It was found that a pseudo-first-order kinetic model based on Langmuir-Hinshelwood one is usable to photodegradation of this compound at all considered buffer pH. In addition to these, the Langmuir-Hinshelwood rate constants, kr for the titled compound at various pH are reported.